Correction of the Lower Face and Neck - Frisenda, Julia L.; Nassif, Paul S. (Facial Plastic Surgery, 2018)
Rejuvenation of the lower face and neck strives to reverse signs of aging while optimizing the patient's natural anatomy. Common features of an aesthetically pleasing lower face include a well-defined and appropriately balanced mandible and an acute cervicomental angle. Correction of the aging lower face and neck is accomplished through multiple surgical interventions, performed either alone or in combination. Determination of appropriate procedures is based on individual anatomic pathology. Intimate knowledge of facial anatomy and the complexity of the aging process is paramount to achieve a natural and aesthetic result. Thorough patient evaluation and counseling should precede any intervention. Specifically, the surgeon should be cognizant of the patient's skeletal structure, soft tissue distribution, muscular anatomy, and skin quality. Appropriate postoperative care and management of complications are vital to success.
Keywords: facial rejuvenation; rhytidectomy; platysmaplasty; submental liposuction; chin augmentation